Identification of Recurrence-Related mRNAs and Noncoding RNAs in Hepatocellular Carcinoma Following Liver Transplantation - Zeng, Qiang; Cao, Jinglin; Niu, Yishan; Zhao, Xin; Wang, Yang; Liu, Wenpeng; Liu, Baowang; Chen, Yajie; Fan, Yize; Dou, Jian (Turkish Journal of Gastroenterology, 2023)
Background: This study aimed to determine whether altered mRNA, long non-coding RNA, and circular RNA expression is related to hepatocellular carcinoma recurrence after liver transplantation.Methods: Five recurrent and 5 non-recurrent primary hepatocellular carcinoma samples were used to perform RNA sequencing. Then, differentially expressed mRNAs, differentially expressed long non-coding RNAs, and differentially expressed circular RNAs between recurrent group and non-recurrent group were identified. In addition, differentially expressed long non-coding RNA/differentially expressed circular RNA–differentially expressed mRNA co-expression network, and competing endogenous RNA (differentially expressed circular RNA/differentially expressed long non-coding RNA–miRNA–differentially expressed mRNA) regulatory network were constructed. Finally, real-time quantitative polymerase chain reaction was performed for verification.Results: Five hundred forty-one differentially expressed mRNAs, 239 differentially expressed long non-coding RNAs, and 16 differentially expressed circular RNAs in the recurrent group were obtained. Gene set enrichment analysis indicated that these differentially expressed mRNAs may affect hepatocellular carcinoma recurrence through multiple pathways, such as E2F, epithelial–mesenchymal transition, G2M, and oxidative phosphorylation. Then, 993 differentially expressed long non-coding RNA–differentially expressed mRNA co-expression pairs and 28 differentially expressed circular RNA/differentially expressed mRNA co-expression pairs were obtained. The competing endogenous RNA network contained 10 circular RNA–miRNA pairs, 12 long non-coding RNA–miRNA pairs, and 36 miRNA– mRNA pairs. Real-time quantitative polymerase chain reaction results showed the same expression trend as RNA-seq results.Conclusion: Our results reveal key mRNAs, long non-coding RNAs, and circular RNAs associated with recurrence in hepatocellular carcinoma patients after liver transplantationCite this article as: Zeng Q, Cao J, Niu Y, et al. Identification of recurrence-related mRNAs and noncoding RNAs in hepatocellular carcinoma following liver transplantation. Turk J Gastroenterol. 2023;34(4):394-405.